EVALITA Evaluation of NLP and Speech Tools for Italian : Proceedings of the Final Workshop 12-13 December 2018, Naples - Viviana Patti
EVALITA is a periodic evaluation campaign of Natural Language Processing (NLP) and speech tools for the Italian language. The general objective of EVALITA is to promote the development of language and speech technologies for the Italian language, providing a shared framework where different systems and approaches can be evaluated in a consistent manner. The diffusion of shared tasks and shared evaluation practices is a crucial step towards the development of resources and tools for NLP and speech sciences. The good response obtained by EVALITA, both in the number of participants and in the quality of results, showed that it is worth pursuing such goals for the Italian language. As a side effect of the evaluation campaign, both training and test data are available to the scientific community as benchmarks for future improvements. EVALITA is an initiative of the Italian Association for Computational Linguistics (AILC) and it is endorsed by the Italian Association for Artificial Intelligence (AI*IA) and the Italian Association for Speech Sciences (AISV).